Meta-Analysis: Effect of School-Based Health Promotion Strategy on Smoking Habits in Adolescents - Bhre Diansyah Dinda Khalifatulloh; Bibit Irawan (Journal of Health Promotion and Behavior, 2022)
Background: Smoking is the biggest preventable cause of death in the world. Tobacco1 is a global problem experienced by both developed and developing countries, the gap in smoking rates between those in high and low socioeconomic groups has widened over the same period. Smoking behavior is not only in adults but also among school students. Peers have previously been reported to play a role in initiating smoking behavior in school-age students. Students' attitudes and behavior related to smoking behavior are influenced by personal knowledge and how peers behave. The purpose of this study was to determine the effect of school-based health promotion strategies on smoking habits in adolescents based on the results of previous studies.Subjects and Method: This study is a meta-analysis study with Population: adolescents. Intervention: using school-based health promotion strategies. Comparison: not using school-based health promotion strategies. Outcome: success in not smoking. The article search process is carried out through the Pubmed web search engine and is a research article published from 2013-2022. The articles obtained will be filtered using the stages according to the PRISM flow diagram.Results: A total of 9 articles used in this study were reviewed and met the requirements for a meta-analysis, the research conducted in these articles was carried out in various continents such as European, America, Africa, Asia, and Australia. Where from the meta-analysis of 9 randomized controlled trial articles, it is known that school-based health promotion strategies increase succes not smoking, and it was statistically significant (OR= 0.49; 95 % CI= 0.43 to 0.56; p= 0.001)Conclusion: The perceived benefit was not statistically significant in predicting the practice of BSE in women.Keywords: smoking, school-based health promotion, youth.Correspondence:Bhre Diansyah Dinda Khalifatulloh. Polytechnic of Jember, East Java. Jl. Mastrip, Krajan Timur, Sumbersari, Jember, East Java 68121. Email: Bhrediansyah98@gmail.com. Mobile: +6281333085809.Journal of Health Promotion and Behavior (2022), 07(02): 132-141DOI: https://doi.org/10.26911/thejhpb.2021.07.02.05